Economic Aspects of Maritime Transport Development - Alexey Yuryevich Smirnov (Управленческое консультирование)
In the article on the basis of the analysis of features of activity of the marine transport of Russia in 2010-2015, dynamics of its key economic indicators are defined tendencies of development of the marine transport in general and its structural components in the fast-changing environmental conditions.